State transitions: a major mortality risk for seasonal species. (8th June 2017) - Landes, Julie; Perret, Martine; Hardy, Isabelle; Camarda, Carlo Giovanni; Henry, Pierre‐Yves; Pavard, Samuel
Abstract: Ageing results from the accumulation of multifactorial damage over time. However, the temporal distribution of this damage remains unknown. In seasonal species, transitions between seasons are critical periods of massive physiological remodelling. We hypothesised that these recurrent peaks of physiological remodelling are costly in terms of survival. We tested whether captive small primates exposed to an experimentally increased frequency of seasonal transitions die sooner than individuals living under natural seasonality. The results show that experiencing one additional season per year increases the mortality hazard by a factor of 3 to 4, whereas the expected number of seasons lived is only slightly impacted by the seasonal rhythm. These results demonstrate that physiological transitions between periods of high and low metabolic activity represent a major mortality risk for seasonal organisms, which has been ignored until now.